Thoracic Empyema: A Narrative Review of Pathophysiology, Diagnosis, and Management - Lalu Dane Pemban Paerdoe; Philip Habib; Shira Putri Wardana; Arwinda Febri Yulianti; Moh. Rizky Yolanda B.S. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Thoracic empyema is a pleural-space infection characterized by purulent pleural fluid or microbiological evidence of infection. It commonly arises from parapneumonic effusion but may also follow aspiration, trauma, thoracic procedures, abdominal infection, fungal infection, or tuberculosis-related pleural disease. This narrative review synthesizes recent evidence on the pathophysiology, diagnosis, and management of thoracic empyema, with attention to decision points relevant to resource-variable health facilities. Literature was identified through PubMed/MEDLINE, NCBI Bookshelf, Thorax/BMJ, European Respiratory Society publications, SpringerLink, MDPI, Google Scholar, and Indonesian databases using terms related to empyema, pleural infection, parapneumonic effusion, drainage, intrapleural therapy, and surgery. Empyema progresses through exudative, fibrinopurulent, and organizing phases; each stage influences pleural-fluid chemistry, loculation, lung expansion, and treatment response. Diagnosis requires an integrated clinical assessment, imaging, and pleural fluid analysis. Frank pus, positive Gram stain or culture, pleural-fluid pH ≤ 7.20, low glucose, and high LDH support drainage. Management combines prompt antibiotics, image-guided pleural drainage, selected intrapleural tissue plasminogen activator/deoxyribonuclease, and timely surgical referral when initial therapy fails. Early ultrasound-based assessment and multidisciplinary escalation may improve outcomes.